(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Ad hoc wireless network is a self configurable infrastructure less network. The lack of infrastructure support in ad hoc networks makes them useful in various applications such as at the disaster site, highway, vast forest, battle field, oceans, etc. Since there is no centralized control in ad hoc network, each node can act as a source, a destination or a router. Ad hoc wireless networks therefore, experience congestion more than the wired networks, leading to jitter and high end to end delays even for moderate traffic which may lead to performance degradation. So it is crucial to analyze the factors which affect the capacity and end-to-end delay in wireless ad-hoc networks. In this paper a G/G/1queuing network model is proposed togain insights into the end-to-end delay in a multi hop wireless ad hoc networks. Queuing network model is unique as it providesclosed form expressions for average end-to-end delay in multihop wireless ad hoc networks. NS2 simulation is conducted in order to verifyÂ and compare the theoretical results.